Application of Al-Uqud Al-Murakkabah in Gold Pawn Products at Pegadaian Syariah - Kalsum, Ummi; Nurnilawati; Husain Insawan (Al-Ulum, 2024)
Research on the application of al-uqud al-murakkabah contracts in Islamic pawnshops has long been a concern of researchers. However, the research is not specific about the application of al-uqud al-murakkabah in Islamic pawnshops. This research aims to find out the application of al-uqud al-murakkabah in gold pawn products in Islamic pawnshops. The methods used are interview and observation. This research theory uses a normative juridical approach, based on the DSN-MUI fatwa and multi-contract criteria. The results of this study indicate that the application of al-uqud al-murakkabah in gold pawn products in Islamic Pawnshops using three contracts, namely the qard contract, rahn contract, and ijarah contract is in accordance with the DSN-MUI Fatwa. However, the application of the three contracts is not carried out separately, which is contrary to the criteria for multi-contracts that are allowed. This research found indications of combining buying and selling with debt and credit, which is prohibited because combining the two contradicts its character and nature.